Prove De Moivre's by induction for the positive integers

First we check the formula for our first case, n=1 where (cosx + isinx)n =cosnx + isinnx (cosx + isinx)1 = cos(1x) + isin(1x) - holds true for n=1 next we assume true for our case n=k(cosx + isinx)k = coskx + isinkxnext we show that if the case for n=k is true, then the case n=k+1 is true.by inputting n=k+1 we get (cosx+isinx)(k+1)=(cosx+isinx)(cosx+isinx)know as we assumed for n=k ,this equals (cosx+isinx)(coskx+isinkx)this gives cosxcoskx +icosxsinkx +isinxcoskx -sinxsinkxsimplifying to (coskxcosx -sinxsinkx) + i(cosxsinkx + sinxcoskx)finally through the compound angle formulae we reach our desired result: (cosx+isinx)k+1 = cos((k+1)x) + isin((k+1)x) conclusion: If n=k holds true, then n=k+1 holds true. Since n=1 holds true we have now shown that De Moivre's theorem holds true for all positive integers.

HS
Answered by Harry S. Further Mathematics tutor

3108 Views

See similar Further Mathematics A Level tutors

Related Further Mathematics A Level answers

All answers ▸

Find the complementary function to the second order differential equation d^2y/dx^2 - 5dy/dx + 6x = x^2


What are differential equations, and why are they important?


Prove by induction that, for all integers n >=1 , ∑(from r=1 to n) r(2r−1)(3r−1)=(n/6)(n+1)(9n^2 -n−2). Assume that 9(k+1)^2 -(k+1)-2=9k^2 +17k+6


Prove that (AB)^-1 = B^-1 A^-1


We're here to help

contact us iconContact usWhatsapp logoMessage us on Whatsapptelephone icon+44 (0) 203 773 6020
Facebook logoInstagram logoLinkedIn logo

© MyTutorWeb Ltd 2013–2025

Terms & Conditions|Privacy Policy
Cookie Preferences